Companion Proceedings of the Web Conference 2020 2020
DOI: 10.1145/3366424.3384370
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Spatial Subdivisions in Urban Mobility with Mobile Phone Data

Abstract: Urban population grows constantly. By 2050 two thirds of the world population will reside in urban areas. This growth is faster and more complex than the ability of cities to measure and plan for their sustainability. To understand what makes a city inclusive for all, we define a methodology to identify and characterize spatial subdivisions: areas with over-and under-representation of specific population groups, named hot and cold spots respectively. Using aggregated mobile phone data, we apply this methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…These improvements will be addressed in future versions of the system. Still, the use of three categories seems to be enough to already tackle on-going problems in mobility, for instance, there are several gaps in mobility that can be explored with two or three variables [52]; thus, Modalflow would allow for urban planners to uncover not only biases in methodological workflows, but also gaps in behaviour that are commonly hidden in traditional analyses and visualizations [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…These improvements will be addressed in future versions of the system. Still, the use of three categories seems to be enough to already tackle on-going problems in mobility, for instance, there are several gaps in mobility that can be explored with two or three variables [52]; thus, Modalflow would allow for urban planners to uncover not only biases in methodological workflows, but also gaps in behaviour that are commonly hidden in traditional analyses and visualizations [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Foursquare allowed its users to broadcast their positions to the social network in the form of a check-in, that is, a record such as "user A was in place B at date C." is includes check-ins in Barcelona and at Camp Nou [23]. e private data consist of aggregated Mobile Phone Data, obtained from an agreement between the Barcelona City Council and Vodafone [24].…”
Section: Communication Networkmentioning
confidence: 99%
“…To infer the demographic and origin of visitors, the information about gender, age, and residence (either local or a tourist) is analyzed. To identify the demographic attributes of visitors to Camp Nou, the results of a previous study [24] are improved using a mobile phone dataset from 2018 created by the mobile phone operator Vodafone for the Barcelona City Hall. e dataset contains aggregated visitor counts in several areas of the city, based on the information gathered from cellular antennas across the city.…”
Section: Spectator Profiling (Society Layer)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, estimates of crimes reported to the police may be affected by the uncertainty arising from the small samples of crimes recorded in small areas (Rosenbaum and Lavrakas 1995). Previous research has shown that crime in Barcelona is highly concentrated in the 'old quarter' (González Murciano and Murrià Sangenís 2020;Maldonado-Guzmán et al 2021), which is characterised by very large concentrations of tourist, hotels, restaurants, museums, bars and clubs, but not necessarily a larger population density (Graells-Garrido et al 2020;Gutiérrez et al 2017). As a result, we would expect survey-based estimates of offence locations to show large concentrations of crime in the city centre, while this may remain hidden when we analyse survey-based estimates of area victimizations.…”
Section: Introductionmentioning
confidence: 99%